Einstein : the life of a genius - Isaacson, Walter (London : Carlton books, 2009)
"Albert Einstein is synonymous with genius. From his remarkable theory of relativity and the famous equation E=mcp2(B, to his concept of a unified field theory, no one else has contributed as much to science in the last century. As well as showing how the brilliant physicist developed his theories, 'Einstein' reveals the man behind the science, from his early years and experiments in Germany and his work at the Swiss Patent Office, to his marriages and children, as well as his role in the development of the atomic bomb and his work for civil rights groups in the United States. Drawing on new research and personal documents belonging to Einstein only recently made available, this book also includes items of rare facsimile memorabilia, to show you more than this scientist's groundbreaking theories."--p. [4] of cover.s
Early years -- Swiss years -- Berlin years -- Princeton years.
Includes index.
Includes translations of facsimiles, p. 90-91.
"Book contains rare facsimile documents and memorabilia"--Cover.
"Einstein's handwritten notes for his lectures on relativity at the Universities of Zurich and Berlin in 1918 and 1919" (2 p.) in pocket on p. 39.
Keywords: Einstein, Albert, -- 1879-1955.; Einstein, Albert, -- 1879-1955 -- Friends and associates; Physicists -- Biography; Relativity (Physics); Unified field theories